2019
DOI: 10.1038/s41467-019-09570-7
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent regulation of sodium channels NaV1.4 and NaV1.5 is controlled by the post-IQ motif

Abstract: Skeletal muscle voltage-gated Na + channel (Na V 1.4) activity is subject to calmodulin (CaM) mediated Ca 2+ -dependent inactivation; no such inactivation is observed in the cardiac Na + channel (Na V 1.5). Taken together, the crystal structures of the Na V 1.4 C-terminal domain relevant complexes and thermodynamic binding data presented here provide a rationale for this iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…During review of this manuscript, a paper was published describing complexes of apoCaM and Ca 2+ /CaM with the Na 1.4 CT, containing both the EF-hand domain and IQ domain (61). The authors found both the apoC-lobe and Ca 2+ /C-lobe to bind to a site nearly identical to the previously identified apoC-lobe binding site in Na V 1.5.…”
Section: Discussionmentioning
confidence: 89%
“…During review of this manuscript, a paper was published describing complexes of apoCaM and Ca 2+ /CaM with the Na 1.4 CT, containing both the EF-hand domain and IQ domain (61). The authors found both the apoC-lobe and Ca 2+ /C-lobe to bind to a site nearly identical to the previously identified apoC-lobe binding site in Na V 1.5.…”
Section: Discussionmentioning
confidence: 89%
“…2019; Yoder et al . 2019). Our structural studies of CaM disease mutants show that different mutations have distinct effects on the structure in the presence of the Ca V 1.2 IQ domain, despite the fact that most, but not all, have a similar functional outcome on CDI: Permanent loss of Ca 2+ binding to EF3, resulting in a distorted C‐lobe.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, the CTerm in both Nav1.4 and Nav1.5 showed functional alteration in a Ca 2+ /CAM‐dependent manner, and disease mutations in CTerm substantially diminished Ca 2+ ‐dependent regulation . In addition, a recent study demonstrated that Ca 2+ ‐dependent inactivation in Nav1.4 could be regulated through an affinity between EFL and CaM . Although not investigated in this study, the possibility of Ca 2+ ‐dependence or CaM expression‐dependence is an important subject that needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, the structure of human Nav1.4 in complex with the β1 subunit was elucidated by cryo‐EM, but the CTerm structure has not yet been solved. However, the crystal structure of the CTerm 168 residues alone was elucidated, showing the structural components of the CTerm in detail. The CTerm is composed of an EF hand‐like motif (EFL) consisting of helices αI‐αV followed by a long α‐helix (helix αVI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation